2014
DOI: 10.1615/heattransres.2014006568
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radiation and Chemical Reaction on Heat and Mass Transfer by Natural Convection in a Micropolar Fluid-Saturated Porous Medium With Streamwise Temperature and Species Concentration Variations

Abstract: In this paper, the problem of coupled heat and mass transfer by a natural-convection boundary-layer fl ow of a micropolar fl uid past a vertical fl at plate in a saturated porous medium with streamwise sinusoidal variations of both the surface temperature and species concentration in the presence of thermal radiation and chemical reaction eff ects is investigated. A suitable set of dimensionless variables is used to transform the governing equations of the problem into a nonsimilar form. The resulting nonsimil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 23 publications
(21 reference statements)
0
5
0
Order By: Relevance
“…Superseding Equations ( 24), ( 25) and ( 26) into Equations ( 19), (20), and ( 21), correlating the harmonic and nonharmonic representations, the negligent and higher-order representations of O ε ( ) 2 , acquires the subsequent pairs of equations q θ ϕ q θ ϕ ( , , ) and ( , , )…”
Section: Defining the Problem And Formulating The Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superseding Equations ( 24), ( 25) and ( 26) into Equations ( 19), (20), and ( 21), correlating the harmonic and nonharmonic representations, the negligent and higher-order representations of O ε ( ) 2 , acquires the subsequent pairs of equations q θ ϕ q θ ϕ ( , , ) and ( , , )…”
Section: Defining the Problem And Formulating The Solutionmentioning
confidence: 99%
“…Gireesha et al 19 have studied the impact of radiation and heat source/sink on mixed convective Dusty fluid over a stretching sheet. Rashad et al 20 have reported natural convection boundary layer analysis of micropolar fluid through porous medium with radiation and chemical reaction. Rashidi et al 21 have presented the effect of thermal radiation on mixed convective flow and heat transfer of viscoelastic fluid over the porous wedge.…”
Section: Introductionmentioning
confidence: 99%
“…Newton's quadratic linearization method combined with the . 27The coefficients in (26) are defined by This article has been accepted for publication in a future issue of this journal, but has not been fully edited. Content may change prior to final publication.…”
Section: Guidelines For Manuscript Preparationmentioning
confidence: 99%
“…Hussanan et al [23] interpreted a Newtonian heating flow of micropolar liquid by free convective along a vertical plate. Some related investigations of micropolar liquids flow are explored in [24][25][26] through several geometry surfaces. Latest advancements in nanotechnology manifested a novel epoch of study known as micropolar nanoliquids.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, laboratory investigations have mainly focused on a single fissure, and the fracture is usually prepared by splitting cylindrical granite in the Brazilian split test (Zhao and Tso 1993;Lu and Xiang 2012;Bai et al 2017;Li et al 2017). In other words, there are few experimental studies on the coupling of seepage and heat transfer in a single fissure (Rashad et al 2014;Wang et al 2017). Zhao conducted hydraulic-thermal experiments on granite samples to study the influence of the temperature field on the permeability of fractures and the convective heat transfer coefficient between the fracture water and the rock matrix.…”
Section: Introductionmentioning
confidence: 99%